Pelatihan 3D City Modeling Menggunakan Google Sketch Bagi Siswa SLTP Advent 1 Palembang - Danny Matthew Saputra; Samsuryadi -; Ahmad Rifai; Rossi Passarella; Sutarno - (Annual Research Seminar (ARS), 2016)
While computer is a common object that most people use on a daily basis, most students only use simple features of the computer. 3D object is known by most students but very few know how to use computer for 3D modeling. 3D modeling is rarely thought in computer classes because most people assumed that it is hard and time consuming, but 3D modeling is one to increase students’ knowledge in geometry and helps train the brain to visualize and think in a 3D environment, which is essential for higher education. Google Sketch is a program that helps build 3D objects easily and in short amount of time. Google Sketch was used as the basis of training 19 students in 3D modeling from making simple 3D object to complex ones. At the end to the of the training every student was able to create a simple city using Google Sketch. The main problem in training student is most of the students rarely use computer and the time constraint.